Improving Student Readiness to Overcome IT-Related Obstacles During Pedagogical Interaction in Post-Soviet Education; Journal of Social Studies Education Research; Vol. 8, № 2 - Luchaninov D. V. Dmitry Vasiljevich; Bazhenov R. I. Ruslan Ivanovich; Shtepa Y. P. Yuliya Petrovna; Nikolaeva N. S. Nataljya Semenovna; Tsytsarev A. A. Andrey Aleksandrovich; Kuimova M. V. Marina Valerievna (2017, 2017)
Title screen